The OECD validation program of the H295R steroidogenesis assay: phase 3. Final inter-laboratory validation study - Hecker, Markus; Hollert, Henner; Cooper, Ralph; Vinggaard, Anne Marie; Akahori, Yumi; Murphy, Margaret; Nellemann, Christine; Higley, Eric; Newsted, John; Laskey, John; Buckalew, Angela; Grund, Stefanie; et al. (Environmental science and pollution research, 2011)
In response to increasing concerns regarding the potential of chemicals to interact with the endocrine system of humans and wildlife, various national and international programs have been initiated with the aim to develop new guidelines for the screening and testing of these chemicals in vertebrates. Here, we report on the validation of an in vitro assay, the H295R steroidogenesis assay, to detect chemicals with the potential to inhibit or induce the production of the sex steroid hormones testosterone (T) and 17β-estradiol (E2) in preparation for the development of an Organization for Economic Cooperation and Development (OECD) test guideline.
Published: 03 October 2010
Gesehen am 28.09.2022